2010
DOI: 10.5194/nhess-10-901-2010
|View full text |Cite
|
Sign up to set email alerts
|

Fractal analysis of subionospheric LF propagation data and consideration of the lithosphere-atmosphere-ionosphere coupling

Abstract: Abstract. Fractal analysis has been applied to the local nighttime data of subionospheric LF propagation, and the fractal dimension is estimated every day in the two distinct frequency ranges (AW: acoustic wave and AGW: atmospheric gravity wave). The data during several years are analyzed for the propagation paths from the Japanese transmitter of JJY to Moshiri (Hokkaido) and to Kochi. As the result of analysis, we come to the conclusion that when we pay attention to the period just around the earthquake, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Finally, we would like to add one more recent result by Imamura et al (2010). Fractal analysis has been applied to the local nighttime data of subionospheric LF propagation, and it is found that when we pay attention to the period just around the EQ, we detect some significant increases in the fractal dimension either in the AW or AGW frequency range.…”
Section: Casementioning
confidence: 99%
“…Finally, we would like to add one more recent result by Imamura et al (2010). Fractal analysis has been applied to the local nighttime data of subionospheric LF propagation, and it is found that when we pay attention to the period just around the EQ, we detect some significant increases in the fractal dimension either in the AW or AGW frequency range.…”
Section: Casementioning
confidence: 99%
“…By considering the exponential damping of the electromagnetic spectrum intensity vs. frequency, several authors (such as Hayakawa et al, 1999;Smirnova et al, 2001;Molchanov et al, 2004;Hobara and Parrot, 2005;Imamura et al, 2010) 2017) reported that the cumulative number of magnetic anomalies (measured nighttime, in geomagnetically quiet conditions) shows a power-law behavior typical of a critical system (with the approach to the critical time and the recovery phase). Based on the similarity of this behavior with that of seismic data, the authors suggest that the LAIC has generated the reported anomalies during the preparation phase of Nepal earthquake.…”
Section: Electromagnetic Field Measurementsmentioning
confidence: 99%